RANCANG BANGUN SISTEM MONITORING OUTPUT KECEPATAN MOTOR INDUKSI TIGA FASA BERBASIS MIKROKONTROLLER DENGAN PENAMPIL PADA MATLAB - Rizana Fauzi; Maryantho Masarrang; Yulius S. Pirade; Sari Dewi (Foristek, 2020)
The use of three-phase induction motors in the industrial world is increasingly growing, in addition to industry, the transportation department is also increasingly using induction motors with the development of transportation models that use electricity. But testing in the performance of induction motors is still not applied. Only the industrial world is able to set test standards for the performance of induction motors. Performance can be seen by monitoring how the output speed of the induction motor. This study aims to create a system that is able to see the performance of the induction motor output in a graph in real time and continuously. In the implementation results, it can be seen that the monitoring system can display a graph that matches the reading of the speed sensor mounted on the induction motor.